Promoting student agentic engagement through curriculum: exploring the Negotiated Integrated Curriculum initiative. Issue 4 (2nd October 2018) - Fitzpatrick, J.; O'Grady, E.; O'Reilly, J.
Abstract : Building on the various works of theorists pertaining to curriculum negotiation, the Negotiated Integrated Curriculum (NIC) initiative detailed in this article attempts to redress the imbalance within curricular decision-making whereby student voice and learner agency is largely absent. The NIC initiative enquires into students' concerns about life and constructs a curriculum to address these concerns as a mechanism that can be shaped to make learning more meaningful through agentic engagement. Based on a longitudinal study of two primary schools, this small scale, exploratory research details the influence of this process on learners and educators and the challenges that were faced during its implementation. The findings of this study examine two main issues: the first is how student voice, particularly around the decision-making of pedagogical activities, can be practically implemented to enhance the perceived relevance of a curriculum; and secondly the process of negotiation between teachers and students to achieve this. Recommendations for the promotion of learner agency and further research are discussed in the context of Irish curriculum reform.